Model Language Tests for the Writing Skill of the Beginner Level Based on CEFR (Common European Framework of Reference) - Ihwan Mahmudi; Shofiyyatun Nisa; Marheni Br Maha; Larasati Hasna (LP2M STIT Palapa Nusantara, 2023)
The Common European Framework of Reference for Language (CEFR), is a method and tool for measuring a person's language skills by using tests according to special procedures for classifying beginner, intermediate, and advanced-level abilities. Therefore, this measurement tool is one of the researchers' goals: to provide examples of various language tests of beginner's writing skills that are classified according to the CEFR measures at levels A1 and A2. This research will analyze examples of writing skill tests for beginners based on the CEFR method. This research was carried out using a desk study design with reading and writing data sources related to language testing forms based on the CEFR method and scoring techniques using desk research methods. The results of this research indicate that the CEFR method is effective for measuring students' abilities and that the writing skill test models can be classified for beginners.